Identifying Perceived Barriers to Seeking Psychological Help Among Rural Youth - Grigoryan, Mariam; Papadopoulos, Eleni (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to identify and explore the perceived sociocultural, structural, and psychological barriers that prevent rural youth in Greece from seeking professional psychological help.Methods and Materials: This qualitative study employed a phenomenological design to capture the lived experiences of rural youth regarding help-seeking for mental health concerns. A purposive sample of 22 participants aged 18–25 from rural areas across Greece was selected. Data were collected through in-depth semi-structured interviews conducted face-to-face and via online platforms until theoretical saturation was reached. Each interview lasted between 45 and 70 minutes and was audio-recorded with participants’ consent. Transcripts were analyzed using Braun and Clarke’s thematic analysis approach, supported by NVivo 14 software to code, categorize, and identify recurring patterns. Ethical standards, including confidentiality, informed consent, and participant anonymity, were strictly maintained throughout the research process.Findings: Analysis revealed four major themes explaining barriers to professional help-seeking: (1) cultural and social stigma, including fear of labeling, gender norms, and family expectations; (2) structural and logistical barriers such as distance, financial hardship, and lack of local services; (3) psychological and personal factors, including low mental health literacy, self-stigma, and fear of self-disclosure; and (4) interpersonal and environmental influences involving peers, family, schools, and community norms. These themes reflect the intertwined effects of cultural identity, limited infrastructure, and individual beliefs on help-seeking behaviors. The results indicate that stigma, limited perceived behavioral control, and restrictive social norms jointly contribute to the low utilization of psychological services among rural youth.Conclusion: The study underscores that addressing help-seeking barriers requires multifaceted interventions integrating cultural sensitivity, mental health literacy, and accessible rural services. Promoting community-based psychoeducation and destigmatization campaigns may enhance openness toward professional psychological support among rural Greek youth.